1996
DOI: 10.1051/jp4:1996867
|View full text |Cite
|
Sign up to set email alerts
|

Damping Capacity of Hypo-Eutectic Zn-Al Alloys

Abstract: Damping capacity of hypo-eutectic Zn-Al alloys as a function of rolling ratio is investigated. Effect of heat treatment after cold rolling on the damping capacity is discussed. Damping tests were carried out using the method of the free decay of vibrations in bending oscillation. With an increase in rolling reduction, the damping capacity was increased. As the results of tensile and hardness testing show, the elongation was increased and hardness was decreased with an increase in rolling reduction. An increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Kurosawa et al [43] investigated the damping capacity of hypo-eutectic Zn-Al alloys as a function of rolling ratio, and they also showed that the hardness of the cold-rolled alloy reduced with an increase in rolling reduction due to the work-softening effect. On the other hand, superplasticity due to high levels of strain rate and decreased grain size can occur in eutectic-based Zn-Al alloys during ECAP.…”
Section: Macro-hardness Testingmentioning
confidence: 97%
“…Kurosawa et al [43] investigated the damping capacity of hypo-eutectic Zn-Al alloys as a function of rolling ratio, and they also showed that the hardness of the cold-rolled alloy reduced with an increase in rolling reduction due to the work-softening effect. On the other hand, superplasticity due to high levels of strain rate and decreased grain size can occur in eutectic-based Zn-Al alloys during ECAP.…”
Section: Macro-hardness Testingmentioning
confidence: 97%
“…The primary deformation mechanism in Zn-Al alloys is grain boundary sliding, and refining the grain size of Zn-22Al alloy is effective in increasing the area of grain boundaries. This, in turn, facilitated easier sliding and enhanced superplastic deformation capability [27], as indicated by Kurosawa et al's research. Two main mechanical processing strategies are commonly employed to achieve superplasticity in Zn-Al alloy ingots: Equal Channel Angular Pressing (ECAP) and Thermomechanical Controlled Processing (TMCP), with the latter involving hot rolling.…”
Section: Hot Rolling Of the Zn-22al Alloy Platesmentioning
confidence: 72%
“…Zn-Al alloys are well known for their high intrinsic mechanical damping and room temperature superplasticity due to the boundaries with high mobility [7,8]. Recently, Kurosawa et al [9] have reported that the mobility of interfaces between equiaxed and ␣ grains is much greater than that concerning lamellar morphology. It implies that higher volume fraction of and ␣ grains having equiaxed morphology would lead to yielding at lower stress in response to increase in interfaces with higher mobility.…”
Section: Resultsmentioning
confidence: 98%